2009
DOI: 10.1002/ijc.24392
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of alpha‐radiation‐induced rat osteosarcomas: Identification of dysregulated genes involved in radiation‐induced tumorigenesis of bone

Abstract: To better understand the molecular basis of radiation-induced osteosarcoma (OS), we performed global gene expression profiling of rat OS tumors induced by the bone-seeking alpha emitter 238 Pu, and the expression profiles were compared with those of normal osteoblasts (OB). The expressions of 72 genes were significantly differentially expressed in the tumors related to OB. These included genes involved in the cell adhesion (e.g., Podxl, Col18a1, Cd93, Emcn and Vcl), differentiation, developmental processes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 62 publications
1
30
0
Order By: Relevance
“…In contrast to these results, most previous studies have suggested that active Wnt signaling contributes to osteosarcoma development [6,7]. Furthermore, it is reported that the Wnt pathway is transcriptionally active in radiation-induced rat osteosarcomas [25], and that the Wnt/β-catenin pathway antagonists, curcumin and PKF118-310, demonstrate anti-tumor activity against human osteosarcoma cells [26]. These seemingly conflicting results suggest that the complexity of this important signaling pathway is still poorly understood in human osteosarcoma [5].…”
Section: Discussionmentioning
confidence: 75%
“…In contrast to these results, most previous studies have suggested that active Wnt signaling contributes to osteosarcoma development [6,7]. Furthermore, it is reported that the Wnt pathway is transcriptionally active in radiation-induced rat osteosarcomas [25], and that the Wnt/β-catenin pathway antagonists, curcumin and PKF118-310, demonstrate anti-tumor activity against human osteosarcoma cells [26]. These seemingly conflicting results suggest that the complexity of this important signaling pathway is still poorly understood in human osteosarcoma [5].…”
Section: Discussionmentioning
confidence: 75%
“…Of these, syntenic sections of 10, 11 and 16 are also lost in cases of human OS [43,44]. Candidate genes of interest on chromosome 7 include the Wnt pathway members DKK3 [45] and Wnt11 [46] which have roles in promoting osteoblast maturation. Chromosome 15 in mouse shows homology with human chromosomes 5, 8, 12 and 22.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it was reported that the Wnt pathway is transcriptionally active in radiation-induced rat OS [22] and Wnt/β-catenin pathway antagonists curcumin and PKF118-310 possess anti-tumour activity against human OS cells [23] . In addition, the Wnt inhibitory factor 1 (Wif1) is silenced in human OS and accelerates radiation-induced OS formation when it is deleted in mice [24] .…”
Section: Discussionmentioning
confidence: 99%